Diastereoselective multi-component tandem condensation: synthesis of 2-amino-4-(2-furanone)-4H-chromene-3-carbonitriles - Gupta, Vijay; Sahu, Debashish; Jain, Shailja; Vanka, Kumar; Singh, Ravi P. (Organic & Biomolecular Chemistry, 2019)
A general strategy for a one-pot stereoselective synthesis of 2-amino-4-(2-furanone)-4H-chromene-3-carbonitriles by reaction of salicylaldehyde, malononitrile and butenolides via a tandem Knoevenagel/Pinner/vinylogous Michael condensation is presented. The beta,gamma-butenolides gave a syn-selective MCR adduct with a dr up to 11.5 : 1. The mechanistic insight into the MCR was obtained by DFT calculations.